Phenotype-dependent effects of EpCAM expression on growth and invasion of human breast cancer cell lines - Martowicz Agnieszka; Spizzo Gilbert; Gastl Guenther; Untergasser Gerold (BMC Cancer, 2012)
Abstract Background The epithelial cell adhesion molecule (EpCAM) has been shown to be overexpressed in breast cancer and stem cells and has emerged as an attractive target for immunotherapy of breast cancer patients. This study analyzes the effects of EpCAM on breast cancer cell lines with epithelial or mesenchymal phenotype. Methods For this purpose, shRNA-mediated knockdown of EpCAM gene expression was performed in EpCAMhigh breast cancer cell lines with epithelial phenotype (MCF-7, T47D and SkBR3). Moreover, EpCAMlow breast carcinoma cell lines with mesenchymal phenotype (MDA-MB-231, Hs578t) and inducible overexpression of EpCAM were used to study effects on proliferation, migration and in vivo growth. Results In comparison to non-specific silencing controls (n/s-crtl) knockdown of EpCAM (E#2) in EpCAMhigh cell lines resulted in reduced cell proliferation under serum-reduced culture conditions. Moreover, DNA synthesis under 3D culture conditions in collagen was significantly reduced. Xenografts of MCF-7 and T47D cells with knockdown of EpCAM formed smaller tumors that were less invasive. EpCAMlow cell lines with tetracycline-inducible overexpression of EpCAM showed no increased cell proliferation or migration under serum-reduced growth conditions. MDA-MB-231 xenografts with EpCAM overexpression showed reduced invasion into host tissue and more infiltrates of chicken granulocytes. Conclusions The role of EpCAM in breast cancer strongly depends on the epithelial or mesenchymal phenotype of tumor cells. Cancer cells with epithelial phenotype need EpCAM as a growth- and invasion-promoting factor, whereas tumor cells with a mesenchymal phenotype are independent of EpCAM in invasion processes and tumor progression. These findings might have clinical implications for EpCAM-based targeting strategies in patients with invasive breast cancer.